Immune cell dysfunctions in breast cancer patients detected through whole blood multi-parametric flow cytometry assay. (3rd March 2016) - Verronèse, E.; Delgado, A.; Valladeau-Guilemond, J.; Garin, G.; Guillemaut, S.; Tredan, O.; Ray-Coquard, I.; Bachelot, T.; N'Kodia, A.; Bardin-Dit-Courageot, C.; Rigal, C.; Pérol, D.; et al.
ABSTRACT: Monitoring functional competence of immune cell populations in clinical routine represents a major challenge. We developed a whole-blood assay to monitor functional competence of peripheral innate immune cells including NK cells, dendritic and monocyte cell subsets through their ability to produce specific cytokines after short-term stimulation, detected through intra-cytoplasmic staining and multi-parametric flow-cytometry. A PMA/ionomycin T cell activation assay complemented this analysis. Comparing cohorts of healthy women and breast cancer (BC) patients at different stages, we identified significant functional alteration of circulating immune cells during BC progression prior to initiation of treatment. Of upmost importance, as early as the localized primary tumor (PT) stage, we observed functional alterations in several innate immune populations and T cells i.e. (i) reduced TNFα production by BDCA-1 + DC and non-classical monocytes in response to Type-I IFN, (ii) a strong drop in IFNγ production by NK cells in response to either Type-I IFN or TLR7/8 ligand, and (iii) a coordinated impairment of cytokine (IL-2, IFNγ, IL-21) production by T cell subpopulations. Overall, these alterations are further accentuated according to the stage of the disease in first-line metastatic patients. Finally, whereas we did not detect functional modification of DC subsets in response to TLR7/8 ligand, we highlighted increased IL-12p40 production by monocytes specifically at first relapse (FR). Our results reinforce the importance of monitoring both innate and adaptive immunity to better evaluate dysfunctions in cancer patients and suggest that our whole-blood assay will be useful to monitor response to treatment, particularly for immunotherapeutic strategies.